Eligibility criteria for Menopausal Hormone Therapy (MHT): a position statement from a consortium of scientific societies for the use of MHT in women with medical conditions. MHT Eligibility Criteria Group. (December 2022) - Mendoza, Nicolás; Ramírez, Isabel; de la Viuda, Esther; Coronado, Pluvio; Baquedano, Laura; Llaneza, Plácido; Nieto, Verónica; Otero, Borja; Sánchez-Méndez, Sonia; de Frutos, Visitación Álvarez; Andraca, Leire; Barriga, Patricio; et al.
Highlights: The objective of this project is to create eligibility criteria for the use of menopausal hormone therapy. This will provide a powerful decision-making tool for managing menopausal symptoms. Abstract: This project aims to develop eligibility criteria for menopausal hormone therapy (MHT). The tool should be similar to those already established for contraception A consortium of scientific societies coordinated by the Spanish Menopause Society met to formulate recommendations for the use of MHT by women with medical conditions based on the best available evidence. The project was developed in two phases. As a first step, we conducted 14 systematic reviews and 32 metanalyses on the safety of MHT (in nine areas: age, time of menopause onset, treatment duration, women with thrombotic risk, women with a personal history of cardiovascular disease, women with metabolic syndrome, women with gastrointestinal diseases, survivors of breast cancer or of other cancers, and women who smoke) and on the most relevant pharmacological interactions with MHT. These systematic reviews and metanalyses helped inform a structured process in which a panel of experts defined the eligibility criteria according to a specific framework, which facilitated the discussion and development process. To unify the proposal, the following eligibility criteria have been defined in accordance with the WHO international nomenclature for the different alternatives for MHT (category 1, no restriction on the use of MHT; category 2, the benefits outweigh the risks; category 3, the risks generally outweigh the benefits; category 4, MHT should not be used). Quality was classified as high, moderate, low or very low, based on several factors (including risk of bias, inaccuracy, inconsistency, lack of directionality and publication bias). When no direct evidence was identified, but plausibility, clinical experience or indirect evidence were available, "Expert opinion" was categorized. For the first time, a set of eligibility criteria, based on clinical evidence and developed according to the most rigorous methodological tools, has been defined. This will provide health professionals with a powerful decision-making tool that can be used to manage menopausal symptoms.